SMS innovation in healthcare; SGEM. International Multidisciplinary Scientific Conference on Social Sciences and Arts; Bk. 1, Vol. 2 - Sakharova E. T. Elena Tarasovna (Sociology and Healthcare, 2014)
Title screen